Calcineurin inhibitor‐free strategies for prophylaxis and treatment of GVHD in children with posterior reversible encephalopathy syndrome after stem cell transplantation. Issue 11 (18th April 2017) - Shkalim‐Zemer, Vered; Konen, Osnat; Levinsky, Yoel; Michaeli, Orli; Yahel, Anat; Krauss, Aviva; Yaniv, Isaac; Stein, Jerry
Abstract: Background: Posterior reversible encephalopathy syndrome (PRES) is a distinct clinico‐radiologic entity that can occur following allogeneic hematopoietic stem cell transplantation, often in the context of treatment with calcineurin inhibitors (CNIs). Procedure: We describe the results of CNI‐free management of 14 children with PRES and review the clinical and radiologic manifestations of their presentation. Results: Discontinuation of CNIs usually resulted in remission of PRES, but patients with established graft versus host disease (GVHD) at the time when treatment was changed often experienced progressive GVHD despite administration of immune suppressive and modulating treatments. All but three patients experienced full neurologic recovery. Nine children died as a result of either GVHD, disease relapse, or severe infection. Conclusions: Discontinuation of CNIs results in neurologic improvement in most cases, but superior alternative immune modulatory treatment is needed to prevent progression of established GVHD.